Considering economic and geological uncertainty in the simulation of realistic investment decisions for CO2-EOR projects in the North Sea. (1st January 2017) - Welkenhuysen, Kris; Rupert, Jort; Compernolle, Tine; Ramirez, Andrea; Swennen, Rudy; Piessens, Kris
Highlights: PSS IV, a techno-economic model for simulating CO2 -EOR projects, is presented. Investment risk and uncertainty play a central role in our methodology. A North Sea case study for the Claymore and Scott field is developed. Case study results show a 30% value increase for the cluster approach. Abstract: The use of anthropogenic CO2 for enhancing oil recovery from mature oil fields in the North Sea has several potential benefits, and a number of assessments have been conducted. It remains, however, difficult to realistically simulate the economic circumstances and decisions, while including the economic uncertainties that surround the relevant markets and policies, and the geological and technological uncertainties that are inherent to dealing with reservoirs and novel technologies in a challenging environment. A new method is proposed here introducing a unique combination of innovations, that include true limited foresight, project flexibility, and the consideration of realistic investment risk. The value of project is here expressed as the Net Present Value (NPV). These elements are combined in the PSS IV simulator. This is a techno-economic simulator for CO2 -enhanced oil recovery (CO2 -EOR), which applies limited foresight and Real Options Analysis to make realistic investment decisions on projects with significant uncertainties and thus risk. Consecutive project decisions are taken based on a decision tree. Multiple oil fields can be approached as a single cluster project, which can provide a lower investment hurdle. In a first test case for PSS IV, the Claymore and Scott oil fields are assessed, and it is shown that economic simulations where EOR projects are regarded as a sum of the individual field assessments will undervalue projects. Simulation results show that results are in a realistic range compared to published numbers, with individual project values for the Claymore field on average of 15.8 €/barrel (bbl; standard deviation SD = 8.3) and for the Scott field of 14.3 €/bbl (SD = 8.6). Due to the inclusion of uncertainties and the application of limited foresight, results range from −6 €/bbl (loss) to over 30 €/bbl. In a cluster configuration 5 €/bbl of additional value is created.